(untitled) (Proceedings of Southern Federal University. Philology, 2020)
In A.P.Chekhov’s drama «Fatherlessness» great attention is paid to the myth of Don Juan and its psychotype. The system of characters in literary context is studied in gender psychology aspect as well. In this process a violation of gender stereotypes and roles, feminity of male characters and masculinity of female ones is noted. The author opposes a scientific knowledge about a woman and a man with romantism in relations between the sexes in literature. It is declared that «Fatherlessness» is the first step to a new art antropology: the old socio-moral principal of typing gives place to a new one – individualization. Attempts of characters to identify themselves with «heroes» in living own life in accordance with literary images are discredited with the author’s irony. In the personal existence of the characters, in behavior men and women only their individual features become decisive and meaningful. Key words: A.P.Chekhov, fatherlessness, Don Juan, psychotype, gender, sex, male, female. DOI 10.18522/1995-0640-2020-2-18-26